Case Report: Telitacicept in the treatment of cSLE-APS: novel therapeutic perspectives on autoimmune thrombotic diseases in children - Liu, Jingyue; Cao, Zhilang; Wang, Yajun; Zheng, Jing (Frontiers in Immunology, 2026)
Thrombotic antiphospholipid syndrome (APS) in Childhood-onset systemic lupus erythematosus (cSLE) remains a therapeutic frontier. Here, we report the first case of telitacicept (a TACI-Fc fusion protein)- induced remission in cSLE related antiphospholipid syndrome (cSLE-APS), where targeted dual BAFF(B cell-activating factor)/APRIL(a proliferation-inducing ligand) inhibition resolved life-threatening infarctions and achieved sustained disease control. During treatment, corticosteroids were successfully discontinued within six months, and a lupus low disease activity state (LLDAS) was maintained. Our findings indicate that telitacicept’s unique ability to regulate B-cell activity could target the dual pathology of cSLE-APS, offering a new therapeutic approach for this serious condition.